2007
DOI: 10.1007/s10658-007-9214-9
|View full text |Cite
|
Sign up to set email alerts
|

Response of UK winter wheat cultivars to Soil-borne cereal mosaic and Wheat spindle streak mosaic viruses across Europe.

Abstract: Twenty-one UK winter wheat cultivars were grown over three seasons at sites with natural inoculum sources of Soil-borne cereal mosaic virus (SBCMV) and Wheat spindle streak mosaic virus (WSSMV) located in France, Italy and the UK. Plants were assessed visually for virus symptoms and leaf extracts were tested for the presence of each virus using enzyme-linked immunosorbent assays (ELISA).Cultivars showing little or no foliar symptoms and low levels of virus in leaf tissue were classified as resistant to each vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
(17 reference statements)
2
12
0
Order By: Relevance
“…In Germany, an increasing acreage is declared as being contaminated with SBCMV and/or WSSMV (Kastirr et al 2006, Huth et al 2007, underlining the necessity for resistant varieties, which are not available so far. European and U.S. American bread and durum wheat cultivars exhibiting a high level of SBCMV resistance (Kanyuka et al 2004, Vallega et al 2006, Budge et al 2008 as well as European and U.S. American bread wheat cultivars showing a high degree of WSSMV resistance (Miller et al 1992, Cadle-Davidson et al 2006, Budge et al 2008) have been reported. Cadle-Davidson et al (2006) also identified the old U.S. American rye variety 'Aroostook' as being resistant to WSSMV.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…In Germany, an increasing acreage is declared as being contaminated with SBCMV and/or WSSMV (Kastirr et al 2006, Huth et al 2007, underlining the necessity for resistant varieties, which are not available so far. European and U.S. American bread and durum wheat cultivars exhibiting a high level of SBCMV resistance (Kanyuka et al 2004, Vallega et al 2006, Budge et al 2008 as well as European and U.S. American bread wheat cultivars showing a high degree of WSSMV resistance (Miller et al 1992, Cadle-Davidson et al 2006, Budge et al 2008) have been reported. Cadle-Davidson et al (2006) also identified the old U.S. American rye variety 'Aroostook' as being resistant to WSSMV.…”
mentioning
confidence: 97%
“…, Budge et al. ) as well as European and U.S. American bread wheat cultivars showing a high degree of WSSMV resistance (Miller et al. , Cadle‐Davidson et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Soil-borne viruses, such as wheat mosaic virus (SBWMV), became a serious threat for European wheat production. In infested fields, yield losses of up to 70% are recorded (Budge et. al.…”
Section: Introductionmentioning
confidence: 99%
“…In the affected areas, yield losses in grain of up to 70% are recorded, at least in wheat (Budge et al 2008).…”
Section: Introductionmentioning
confidence: 99%